2021
DOI: 10.20944/preprints202101.0611.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation and Projection of Mean Surface Temperature Using CMIP6 Models Over East Africa

Abstract: This study evaluates the historical mean surface temperature (hereafter T2m) and examines how T2m changes over East Africa (EA) in the 21st century using CMIP6 models. An evaluation was conducted based on mean state, trends, and statistical metrics (Bias, Correlation Coefficient, Root Mean Square Difference, and Taylor skill score). For future projections over EA, five best performing CMIP6 models (based on their performance ranking in historical mean temperature simulations) under the shared socioeconomic pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Since this study and ours mostly considered different GCMs and different temperature parameters; mean temperature in the former and maximum and minimum temperature in the later, in their ability to replicate observed temperature, conclusions as to the generally performing models based on both studies is undeterminable. This is because, though some common models such as IPSL-CM6A-LR and MPI-ESM2-LR were found to have good performances as seen in (Ayugi et al, 2021b) for mean temperature and in this present study for minimum temperature. However, IPSL-CM6A-LR was found to be the second least ranking model for maximum temperature in this study.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Since this study and ours mostly considered different GCMs and different temperature parameters; mean temperature in the former and maximum and minimum temperature in the later, in their ability to replicate observed temperature, conclusions as to the generally performing models based on both studies is undeterminable. This is because, though some common models such as IPSL-CM6A-LR and MPI-ESM2-LR were found to have good performances as seen in (Ayugi et al, 2021b) for mean temperature and in this present study for minimum temperature. However, IPSL-CM6A-LR was found to be the second least ranking model for maximum temperature in this study.…”
Section: Discussionmentioning
confidence: 45%
“…In the eastern part of East Africa, covering Kenya, Rwanda, Tanzania, Uganda, and Burundi, thirteen CMIP6 temperature GCMs were used in evaluating mean surface temperature (Ayugi et al, 2021b) by employing statistical metrics, mean state, and trends. The study found that most of the GCMs overestimated the mean annual temperature with few underestimating it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRU data is preferred over other gridded datasets because the data have been developed from a relatively large number of in‐situ data with a longer temporal scale (Harris et al ., 2014; Ahmed et al ., 2019). Several studies have tested the CRU data and its validity in various parts of Africa (Shiru et al ., 2019, 2020; Lim Kam Sian et al ., 2021; Ayugi et al ., 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…Statistical approaches such as root mean square difference (RMSD), correlation coefficient (CC), and mean bias (B) were used to determine the skilfulness of the CMIP6 GCMs in reproducing Tmin, Tmax, and Tmean against the corresponding CRU datasets. Other studies (e.g., Babaousmail et al ., 2019, 2021; Ongoma et al ., 2019; Ayugi et al ., 2020, 2021b, 2021a; Ngoma et al ., 2021a, 2021b) have used the metrics in evaluating model simulation of climate variables. The mathematical formulas of the metrics employed are shown in Equations () and (); Bgoodbreak=1Nk=1N()Migoodbreak−Oi2.25emRMSDgoodbreak=1Nk=1NMnormaliOnormali2 CCgoodbreak=k=1n()Oigoodbreak−trueOnormali¯()Migoodbreak−trueMnormali¯k=1n()Oigoodbreak−trueOnormali¯2k=1n()Migoodbreak−trueMnormali¯2 …”
Section: Methodsmentioning
confidence: 99%